2009
DOI: 10.1055/s-0029-1234508
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antileishmanial activity of hydroalcoholic extract, fractions, and compounds isolated from leaves of Piper ovatum Vahl against Leishmania amazonensis

Abstract: We assessed the biological activity of a crude extract, a mixture of several fractions, and a pure compound obtained from Piper ovatum Vahl against promastigote and amastigote forms of Leishmania amazonensis. The medicinal plant P. ovatum is used popularly as an anesthetic and anti-inflammatory. This study included the extraction process and bioassay-guided fractionation by the adsorption chromatography and Sephadex LH-20 method. A progressive increase in the antileishmanial effect was observed in the course o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…PNH and PNE at 200 mg/ kg bw rendered remarkable protection whereas partial recovery from disease was evident at 100 mg/kg bw dose. Despite several antileishmanial studies from numerous plants of the genus Piper ( Torres-Santos et al, 1999 ; Hermoso et al, 2003 ; Bodiwala et al, 2007 ; Sarkar et al, 2008 ; Flores et al, 2009 ; Rodrigues-Silva et al, 2009 ; Monzote et al, 2010 ; Cruz et al, 2011 ; Carrara et al, 2013 ), there are no reports on in vivo antileishmanial potential of P. nigrum extracts or pure compounds isolated from P. nigrum to the best of our knowledge. However, in vivo antileishmanial efficacy of PIP and its different formulations have been earlier reported.…”
Section: Discussionmentioning
confidence: 99%
“…PNH and PNE at 200 mg/ kg bw rendered remarkable protection whereas partial recovery from disease was evident at 100 mg/kg bw dose. Despite several antileishmanial studies from numerous plants of the genus Piper ( Torres-Santos et al, 1999 ; Hermoso et al, 2003 ; Bodiwala et al, 2007 ; Sarkar et al, 2008 ; Flores et al, 2009 ; Rodrigues-Silva et al, 2009 ; Monzote et al, 2010 ; Cruz et al, 2011 ; Carrara et al, 2013 ), there are no reports on in vivo antileishmanial potential of P. nigrum extracts or pure compounds isolated from P. nigrum to the best of our knowledge. However, in vivo antileishmanial efficacy of PIP and its different formulations have been earlier reported.…”
Section: Discussionmentioning
confidence: 99%
“…DMSo at the maximum concentration used (1%) did not interfere with parasite growth. RoDRIGUES-SILVA et al (2009) reported the in vitro activity of hydroalcoholic extract and fractions of Piper ovatum, against Leishmania amazonensis. A progressive increase in the antileishmanial effect was observed in the course of the fractionation.…”
Section: Resultsmentioning
confidence: 99%